Dimensionamento otimizado de vigas mistas alveolares por meio de algoritmos genéticos - Ramos, Jose Ronaldo Soares (2019)
The objective of this work is to present the formulation of the optimization problem and its applications for composite beams of steel e concrete with web openings. The implementation of the program was made in Matlab platform using the guide tool. The formulation of the problem was based on the studies of Lawson e Hicks (2011), described in the European Design Guide SCI Publication P355 with appropriate adaptations to NBR 8800:2008. The optimization problem was solved using Genetic Algorithm, because it is a discrete problem. Validation examples are presented and a study of the predominant collapse modes has been done to show the application and the advantages of the proposed formulation. A numerical analysis by the Finite Element Method was made for to demonstrate the predominant mode of collapse. The results found pointed out that the application of the genetic algorithm for this type of problem leads to more economical solutions when compared to the examples found in the specialized literature